Correlation between fitness and body size in handball players - Massuca, L. M.; Fragoso, I.; Alves, F. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
This study aims to determine the relationship between body size and fitness characteristics of Portuguese handball players. A total of 210 male handball players (age, 23.73 ±5.25 years) participated in this study. Two anthropometric measures were taken from each player, i.e., body mass (in kg) and stature (in cm). Fitness profiling considered 18 variables: 30-m sprint time (30-m, s); (2) Squat jump (SJ) and countermovement (CMJ) height, height ratio and Pavg; (3) SJ adapted to arms (SJA) and CMJ adapted to arms (CMJA), height and height ratio; (4) Handgrip indices, namely dominant, non-dominant, mean score of dominant and non-dominant (mean) and difference between dominant and non-dominant; (5) Number of executions (#) in sit-up test (in 60-s); (6) Distance (m) and the position (1, <1000-m; 2, [1000-m;1300-m[; 3, [1300-m;1600-m[; 4, .1600-m) in Yo-Yo Intermittent Endurance Test - Level 2 (Yo-Yo IE2). The Pearson product moment correlation coefficient was used to assess the relationship between selected parameters. The results of the present study show that heavier handball players performed worse in 30-m sprint, vertical jump height, sit ups and Yo-Yo IE2 distance. Moreover, players with higher body mass or stature performed better in handgrip strength (dominant, non-dominant and mean) and average power in vertical jump. However, the indexes in jump height ratio (SJ and CMJ) were inferior. This is in favour of strength and power activities but, represents a limiting factor for weight-bearing activities such as running endurance efforts. The present study suggested that stature is the most significant predictor of vertical jump performance. However, results don't support that body mass is the most significant predictor of 30-m sprint performance. Nevertheless, according to the gained results, it seems that, in handball players, fitness performances were highly dependent of individual anthropometric characteristics. Pearson Correlations